The content of exchangeable potassium in the soil depending on the method of tillage and meteorological factors - Pogromska, Ya. A. (AgroChemistry and Soil Science, 2021)
The article is a continuation of a series of publications on the results of the study of nutrient elements in the soil-plant system against the background of global and regional climate change, given the possibility of minimizing tillage. In the conditions of stationary field experiment on ordinary chernozem (Calcic Chernozem) in the Donetsk region for five years (1994-1998) it was monitored the content of exchangeable potassium in the arable layer of the soil under the row crop corn within the grain-growing crop rotation on the options of plowing and subsurface non-turning tillage under the same mineral fertilizer system. At the same time, the dynamics of precipitation and air and soil temperature were recorded. According to the results of research, it is a steady effect of meteorological factors on the level of potassium nutrition of plants and a general tendency to decrease the average level of exchangeable potassium contents in the soil under vegetative plants of maize within the arable layer, mainly due to layers of 10-20 cm and 20-30 cm. It is shown that for plowing the optimum of humidity of the previous year is characterized by hydrothermal coefficient of Selianinov (HTC) 1.0, and for subsurface non-turning tillage - 1.25. With a very dry (HTC < 0.5) or excessively wet year (HTC > 1.5), subsurface non-turning tillage may be more favorable for potassium mobility. But within the HTC 0.5-1.5 is more acceptable plowing. It is determined that the refusal to plowing leads to a decrease in the dependence of potassium mobility in the soil layer 0-30 cm on temperature, protecting from temperature fixation of potassium, and enhances the influence of the humidification regime in May. But dry and cool autumn is a likely cause of reduced potassium mobility without plowing. All conclusions are confirmed by the results of correlation, regression and variance (ANOVA) analysis.